IMPLEMENTASI PROGRAM PEMBERDAYAAN PEREMPUAN RAWAN SOSIAL EKONOMI (PRSE) DI KECAMATAN KORONCONG KABUPATEN PANDEGLANG - khaeriyah, siti; Jumanah, Jumanah (JOURNAL OF GOVERNMENT (Kajian Manajemen Pemerintahan dan Otonomi Daerah), 2018)
Women Prone to Socio-Economic have a definition that is an adult married, unmarried, married or widowed woman and does not have enough income to be able to meet basic daily needs. Based on field observations there are several obstacles encountered in the implementation of the assistance program provided. First, the program objectives have not been achieved.Second, limited resources in the implementation of the program.Third, the program benefits have not been absorbed to the maximum. Fourth, there is no change of degree achieved. This type of research is descriptive qualitative, and the sampling method used is purposive sampling technique where sampling technique that only take sampling unit in accordance with the purpose of the researcher, to test the validity of data used triangulation data. Data obtained from several sources through interviews, documentation, and observasi.Harapan future government Pandeglang better in providing appropriate assistance programs to Women Prone Social Economics (PRSE), so the goal of the program can be achieved well.